Altered Metal Homeostasis Associates with Inflammation, Oxidative Stress, Impaired Glucose Metabolism, and Dyslipidemia in the Crosstalk between Childhood Obesity and Insulin Resistance - Álvaro González-Domínguez; María Millán-Martínez; Jesús Domínguez-Riscart; Rosa María Mateos; Alfonso María Lechuga-Sancho; Raúl González-Domínguez (MDPI AG, 2022)
Metals are redox-active substances that participate in central biological processes and may be involved in a multitude of pathogenic events. However, considering the inconsistencies reported in the literature, further research is crucial to disentangle the role of metal homeostasis in childhood obesity and comorbidities using well-characterized cohorts and state-of-the-art analytical methods. To this end, we studied an observational population comprising children with obesity and insulin resistance, children with obesity without insulin resistance, and healthy control children. A multi-elemental approach based on the size-fractionation of metal species was applied to quantify the total content of various essential and toxic elements in plasma and erythrocyte samples, and to simultaneously investigate the metal fractions conforming the metalloproteome and the labile metal pool. The most important disturbances in childhood obesity were found to be related to elevated circulating copper levels, decreased content of plasmatic proteins containing chromium, cobalt, iron, manganese, molybdenum, selenium, and zinc, as well as the sequestration of copper, iron, and selenium within erythrocytes. Interestingly, these metal disturbances were normally exacerbated among children with concomitant insulin resistance, and in turn were associated to other characteristic pathogenic events, such as inflammation, oxidative stress, abnormal glucose metabolism, and dyslipidemia. Therefore, this study represents one-step further towards a better understanding of the involvement of metals in the crosstalk between childhood obesity and insulin resistance.